Hatching, survival and deformities of piracanjuba (Brycon orbignyanus) embryos subjected to different cooling protocols - Faria Paes, Maria do Carmo [UNESP]; Silva, Regiane Cristina da [UNESP]; Nascimento, Nivaldo Ferreira do [UNESP]; Valentin, Fernanda Nogueira [UNESP]; Senhorini, Jose Augusto; Okada Nakaghi, Laura Satiko [UNESP] (Elsevier B.V., 2014)
Groups of one hundred Brycon orbignyanus embryos at the stage of blastopore closure were subjected to different cooling protocols. Different combinations and concentrations of cryoprotectants were tested: sucrose, methanol, ethylene glycol and dimethyl sulfoxide (Me2SO); at different temperatures (0.0 +/- 2.0 degrees C and 8.0 +/- 2.0 degrees C) and refrigeration times (6, 10, 24, 72 and 168 h), with the exception of the positive control (incubation without previous cooling). At the end of each refrigeration time, the embryos were acclimatized, rehydrated and incubated to determine hatching, survival and deformity rates. Morphological analysis of embryos was also carried out. The results showed that temperature and refrigeration time are critical factors for embryo survival. No embryos survived after 24, 72 and 168 h of refrigeration. Furthermore, when the refrigeration time increased from 6 to 10 h and the temperature decreased from 8.0 +/- 2.0 degrees C to 0.0 +/- 2.0 degrees C, mortality rates increased significantly. It was also found that in all protocols dead eggs and/or larvae with some degree of deformity were present. The main larval deformities observed were the malformation of the head, tail, yolk sac, vertebral column and eyes. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Cryobiology; Fish; Reproduction; Conservation; Anomalies